2020
DOI: 10.3389/fgene.2020.00892
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prostate Cancer-Related Circular RNA Through Bioinformatics Analysis

Abstract: Background: Prostate cancer (PCa) is one of the most common malignant tumors worldwide. Accumulating evidence has suggested that circular RNAs (circRNAs) are involved in the development and progression of various cancers, and they show great potential as novel biomarkers. However, the underlying mechanisms and specific functions of most circRNAs in PCa remain unknown. Here, we aimed to identify circRNAs with potential roles in PCa from the PCa expression profile. Methods: We used data downloaded from the Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Genes can be targeted to identify upstream miRNAs. A total of 10 miRNAs were identified in this study, with studies finding hsa-let-7f-2-3p to be associated with bladder cancer progression (He et al, 2018), hsa-mir-1244 (Li et al, 2017) and hsa-mir-1197 (Yang et al, 2020) to be associated with lung cancer, and hsa-mir-1253 (Wu et al, 2020) to be associated with prostate cancer, and other miRNAs not found to be associated with cancer. It has been established that circRNA can function as "sponges" to recruit the corresponding miRNAs by interacting with miRNA binding sites, thereby playing an indirect role in regulating gene expression (Bai et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Genes can be targeted to identify upstream miRNAs. A total of 10 miRNAs were identified in this study, with studies finding hsa-let-7f-2-3p to be associated with bladder cancer progression (He et al, 2018), hsa-mir-1244 (Li et al, 2017) and hsa-mir-1197 (Yang et al, 2020) to be associated with lung cancer, and hsa-mir-1253 (Wu et al, 2020) to be associated with prostate cancer, and other miRNAs not found to be associated with cancer. It has been established that circRNA can function as "sponges" to recruit the corresponding miRNAs by interacting with miRNA binding sites, thereby playing an indirect role in regulating gene expression (Bai et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…CircRNAs are widespread functional RNAs that promote or suppress the progression of PC, 14 and multiple abnormally expressed circRNAs have been identified to be PC‐related 22,26,27 . Pro‐oncogenic circRNAs such as hsa_circ_0000735 and anti‐oncogenic circRNA such as circFOXO3 are connected with the progression of PC, as well as DTX resistance 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs could act as miRNA sponges through a competitive endogenous RNA (ceRNA) network to master the expression of target mRNAs 22,23 . The present study aimed to investigate the expression and role of circDPP4 in cell progression of PC cells both in vitro and in vivo and DTX cytotoxicity in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…identified 60 circRNAs differentially expressed between PCa tissues and normal tissues, and used bioinformatics to predict three circRNA-miRNA-mRNA interaction axes. 62 …”
Section: Circrna Expression Profiles In Pcamentioning
confidence: 99%
“…Using the GSE140927 dataset, Wu et al identified 60 circRNAs differentially expressed between PCa tissues and normal tissues, and used bioinformatics to predict three circRNA-miRNA-mRNA interaction axes. 62 In general, there are a large number of aberrantly expressed circRNAs between PCa tissues and normal tissues. In most studies, the number of circRNAs downregulated was higher than those upregulated.…”
Section: Circrna Expression Profiles In Pcamentioning
confidence: 99%